Reduced impact logging: putting research results into practice - Dykstra, D.P. (1998)
Since the United Nations Conference on Environment and Development (UNCED) was held in 1992 attitudes toward management of tropical forest has changed. Previously, environmental group opposed any logging at all in such forests. Around the same time, many development agencies and international non-governmental organizations began promoting reduced-impact logging as a strategy for sustainable of tropical forests. Codes of forest practice are sets of guidelines which are designed to help foresters in government agencies and forest enterprises select practices to be followed in carrying out forest management and utilization operations. FAO recently published the FAO Model Code of Forest Harvesting Practice. It is intended to be used as a reference by FAO member nations which are contemplating the preparation of their own codes of forest harvesting practice. It has been prepared to provide information on a range of practices that are likely to be acceptable under various conditions, and also on practices which may reduce timber or non-timber resource values. In doing this, the FAO Model Code make two assumptions: First, that it is necessary to know what practices are technically and economically feasible. Second, that it is possible to conduct forest harvesting operations in ways that are consistent with sustainable forest management. The techniques to practice the reduced-impact logging are discussed in this paper. For the most part of the techniques to implement it only require relatively minor modifications. Government policies play an important role to ensure that these practices are adopted widely. (YS)